Periodic vicissitudes of different concentrations of a developed prototype killed S. aureus mastitis vaccine on immune modulators, mediators and immunoglobulins in cows - Hambali, Idris Umar; Abdullah, Faez Firdaus Jesse; Bhutto, K. R.; Mohd Azmi, M. L.; Wahid, A. H.; Zakaria, Z.; Odhah, M. N.; Arsalan, M.; Muhammad, N. A.; Jefri, M. N. (Springer Nature, 2019)
Mastitis is the inflammation of the mammary gland due to microbial infiltration causing a reduced mammary function. This study aims at developing a vaccine using Malaysian local isolate of Staphylococcus aureus and evaluating serum amyloid A, Interleukin-10, IgM and IgG responses periodically. Four bacterin concentrations (10⁶, 10⁷, 10⁸ and 10⁹ cfu/ml of the local isolate of S. aureus) were adjuvanted with aluminium potassium sulphate. Thirty cows grouped into 4 treatment groups (G-) were vaccinated (2 ml) intramuscularly, with a fifth G-A as control. The mean concentration (MC) of serum amyloid A (SAA) was significantly different (sig-d) (p ˂ 0.05) in G-D at 0 h post vaccination (PV), 3 h PV, 24 h PV, weeks 1, 2, 3 and 4 PV (6-, 15-, 5-, 12-, 11-, 4- and 11-fold increased (FI) respectively). The MC of serum amyloid A was also sig-d in G-E at 0 h PV, weeks 1, 2 and 4 PV (3, 8, 5 and 8 FI respectively). The MC of IL-10 was sig-d in G-D and C at 3 h PV and week 2 PV (5 and 2 FI respectively). The IgM MC was sig-d in G-B and C at 3 h PV (5 and 6 FI respectively), at 24 h PV (5 and 9 FI respectively), at week 3 PV(2 and 2 FI respectively) and week 4 PV (3 and 4 FI respectively). The MC of IgG was sig-d in G-E at 0 h, 3 h and week 3 PV(5, 6 and 2 FI respectively) and in G-D at weeks 1–4 (3, 3, 3 and 5 FI respectively). In conclusion, elevated levels of SAA, IgG and IL-10 in G-D(10⁸) informed our choice of best dosage which can be used to evoke immunity in cows.